2001
DOI: 10.1115/1.1385519
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Residential-Sized GAX Absorption Chiller

Abstract: This research effort involved experimentally testing an advanced-cycle, ammonia-water absorption chiller with a cooling capacity of 17.6 kW (5 refrigeration tons (RT)). The system was a generator-absorber heat exchange (GAX) cycle and was sized for residential and light commercial use, where very little absorption equipment is currently used. The components of the cycle were assembled with instrumentation, including flow meters, pressure transducers, and thermocouples. The findings of the research were cycle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The GAX cycle is a system that provides the highest coefficient of performance of any single effect absorption cycle. Theoretical studies report for GAX systems COP th 30% higher than single effect cycles [4,5]; recently some experimental studies of GAX cycle for air-conditioning and refrigeration have been reported [6,7]. The GAX technology was theoretically developed by Altenkirch in 1913 [4], but the first prototype working with natural gas was constructed in 1980.…”
Section: Introductionmentioning
confidence: 98%
“…The GAX cycle is a system that provides the highest coefficient of performance of any single effect absorption cycle. Theoretical studies report for GAX systems COP th 30% higher than single effect cycles [4,5]; recently some experimental studies of GAX cycle for air-conditioning and refrigeration have been reported [6,7]. The GAX technology was theoretically developed by Altenkirch in 1913 [4], but the first prototype working with natural gas was constructed in 1980.…”
Section: Introductionmentioning
confidence: 98%
“…A research group in Ohio (Priedeman & Garrabrant, 2001) experimentally tested the performance of a residential sized gas-fired absorption chiller with GAX. The capacity of the tested heat pump was 17.5 kW (5 refrigeration tons).…”
Section: Different Ahp Configurationsmentioning
confidence: 99%
“…A recommendation that is common among absorption heat pump systems, including gas-fired systems, is the incorporation of a GAX in the cycle (Kang et al, 2000;Garimella et al, 2016;Phillips, 1990;Velázquez & Best, 2002). The GAX cycles have consistently shown to boost the COP values and offer energy and cost saving potential (Priedeman & Garrabrant, 2001;Velázquez & Best, 2002;Engler et al, 1997). However, a GAX cycle alone will not maximize the potential of the GAHP system, reduction of part load and maximizing time that the GAHP operates at full load is crucial in preventing unnecessary losses that reduce the efficiency of the overall system (Velázquez & Best, 2002).…”
Section: System Optimization and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the influence of the sink temperature on the system performance, they also analyzed the influence of other parameters such as the flow rate in the GAX heat transfer loop. Priedeman et al (2001) developed a 17.5 kW GAX system which employs NH 3 eH 2 0 as the working fluid and natural gas as the heat source. The system was tested at an ambient temperature of 35 C. The system attained a COP of 0.68 under a full load condition.…”
Section: Introductionmentioning
confidence: 99%